Evaluation of blood compatibility of plasma deposited heparin-like films and SF6 plasma treated surfaces - Perrenoud, Ivanira Antunes [UNESP] (2010)
In devices used in open-heart surgery and dialysis, blood must be continuously processed using extracorporeal circuits composed of peristaltic pumps and active components such as specifc flters and oxygenators. Several procedures have been employed to avoid blood coagulation induced by contact with the artifcial surfaces of such devices. Often heparin, a bioactive protein able to prevent clot formation, is employed. In this work, we have used heparin-containing gas plasmas to evaluate the possibility of depositing adherent anticoagulant flms onto PVC and glass surfaces. The flms were produced by radiofrequency plasma enhanced chemical vapor deposition from heparin/isopropanol and heparin/hexamethyldisiloxane solutions. In addition, the effects of exposure to SF6 plasmas on the compatibility of such surfaces have also been investigated. The blood compatibility was evaluated through the determination of the density of platelets and fbrinogen and activated partial thromboplastin (APTT) and prothrombin times (PT) of human blood freshly collected and after contact for 2.5 hours with different surfaces. The deposited flms were also characterized by infrared spectroscopy, contact angle and surface energy measurements. The coagulation time of blood, placed in contact with glass substrates coated by PECVD flms of heparin/isopropanol mixtures, and in contact with SF6 plasma-treated PVC, increased by about 60 and 20%, respectively, compared to the values measured with untreated samples.